Railway Communication Network: A Case Study for Mobile Quality of Service - Cutifa Safitri (IT for Society, 2020)
Trains, nowadays, are becoming a popular choice for a fast, comfortable, and cheaper way to travel. Train’s passengers on a long journey tend to occupy their time by accessing content through mobile devices. Cisco predicted Smartphone traffic will exceed PC traffic by 2020. With the increasing growth of content exchanged, there is a rising demand for managing content for mobile users. Without a significant improvement in railway network infrastructure, the Quality of Service (QoS) for communication in-carriage will degrade, compromising passengers’ experience in mobile communication. Moreover, due to the nature of the railway network that has to support a large group of users in a long journey period, the requested contents are usually bandwidthintensive with the need for continuous mobility support. In order to ensure mobile Quality of Service (mQoS), intelligent & dynamic content management is required to facilitate content distribution. Currently implemented a method to manage mobility heavily relies on a host-to-host connection. A proposal by Future Internet Architecture introduces content-centric networking with built-in mobility. The present paper consider scalability and QoS in high-speed mobility. Therefore, by using a content-centric network proposal, this research aims to propose railway communication networks that provide the solution of mobile QoS.